36 Life stories by Qulutanguaq Jeremiassen (part 1) - Leonard, Stephen Pax (2011)
This is the first in a series of recordings, documenting the life of Qulutanguaq Jeremiassen. Qulutanguaq is the oldest member of the community (88 years old) and is considered the best living story-teller. Qulutanguaq starts his story by telling us in detail how he celebrated his third birthday .wav and .mp3 audio file